ONTOLOGICAL SECURITY OF AN INDIVIDUAL: ATTACHMENT STYLES AND COPING STRATEGIES - Hapon, Nadiya; Vovk, Anna; Snyadanko, Iryna; Fedyna, Liliya (Journal of Education Culture and Society, 2021)
Aim. The aim of this paper is to theoretically substantiate individual’s attachment as a need for ontological security, to outline the educational aspects of supporting the ontological security, and to empirically investigate the attachment styles and coping strategies of individuals in early and middle adulthood. Methods. The article is based on an extensive review of the literature, which involves the use of such methods as interpretation (of previously unexplained psychological aspects of ontological security) and comparative analysis (of the views of Ronald Laing and family psychotherapists). An empirical study was conducted. The study group consisted of 90 persons: 45 male and 45 female, at the age of early and middle adulthood. The research used a number of psychological methods to study different types of attachments, relationships, personality traits and coping strategies that help overcome ontological insecurity. The method of statistical and mathematical analysis of results was also applied. Results. Ontological security is a marker of positive types of attachment. Our empirical research has shown that people with anxious attachment more often overcome ontological insecurity by positively rethinking the problem, which can lead to an underestimation of the possibilities of its effective solution. People with a reliable attachment are ontologically secure due to mutual trust, responsibility, problem analysis and planning, which eliminate escape strategies and problem avoidance. Conclusions. Ontological security-insecurity manifests itself in different types of attachments and corresponding coping strategies. The results showed the importance of developing and adapting the methodology of ontological protection for Ukrainian socio-cultural realities. This technique is being prepared to be operationalized with the scales of psychological techniques used in this study.